Basic aspects of the compliance with discipline and legitimacy within the official activities of police - Сіроха, Дмитро Ігорович; Сіроха, Д. І.; Сироха, Дмитрий Игоревич; Sirokha, Dmytro I.; Фелик, Василь Іванович; Фелик, В. І.; Фелик, Василий Иванович; Felyk, Vasyl I.; Подорожній, Євген Юрійович; Подорожній, Є. Ю.; Подорожный, Евгений Юрьевич; Podorozhnii, Yevhen Yu.; et al. (Universidad de la Amazonia, 2020)
The author of this article has studied the main features of the compliance with discipline and legitimacy by the employees of the agencies of the National Police of Ukraine and special division of the Corps of Operative and Forceful Action. The scientific views on the essence of these terms have been also considered. The author has formed and provided own concepts of the terms of «discipline» and «legitimacy» in the process of serving in the Corps of Operative and Forceful Action. The classification of the types of service discipline has been offered and the features of each of them have been determined. According to the results of the study the author has suggested concrete steps to improve these legal categories within the service process, by amending the relevant specialized legislative acts. Based on the results of the study, it was concluded that discipline in the police is the strict and accurate execution by police in accordance with the procedure and rules established by the legislation of Ukraine, official duties, the exercise of their powers and compliance with job restrictions in the course of their official activities. The objective of this article is to study and analyze the existing regulatory base regulating the activities of the National Police of Ukraine and, in particular, the special division COFA, to establish the main features of discipline and legitimacy by the employees, as well as the development of specific ways to improve these legal categories in the process of service. The research was carried out on the basis of formal-logical, comparative-legal and purely legal techniques.

В данной статье рассмотрены основные особенности соблюдения дисциплины и законности сотрудниками органов Национальной полиции Украины и спецподразделения Корпуса оперативно-внезапного действия. Также рассмотрены научные взгляды на суть данных терминов. Сформированы и представлены авторские понятия терминов «дисциплина» и «законность» в процессе прохождения службы в Корпусе оперативно-внезапного действия. Предложено классификацию видов служебной дисциплины и определены особенности каждого из них. За результатами исследования предложены конкретные шаги усовершенствования этих правовых категорий в процессе службы, с помощью внесения изменений в профильные законодательные акты. Отмечено, что дисциплина в органах полиции - это строгое и точное выполнение полицейскими в соответствии с порядком и правилами, установленными законодательством Украины, служебных обязанностей, реализация ими своих полномочий и соблюдение ограничений по должности в процессе своей служебной деятельности. Целью данной статьи является изучение существующей нормативно-правовой базы, регулирующей деятельность органов Национальной полиции Украины и, в частности, спецподразделения КОРД, установление основных особенностей соблюдения дисциплины и законности служащими, а также разработка конкретных путей усовершенствования указанных правовых категорий в процессе службы. Исследование проводилось с использованием формально-логического, сравнительно-правового и чисто юридических методов.

У даній статті розглянуті основні особливості дотримання дисципліни та законності працівниками органів Національної поліції України та спецпідрозділу Корпусу оперативно-раптової дії. Також розглянуті наукові погляди на зміст даних термінів. Сформовані та подані авторські поняття термінів «дисципліна» і «законність» в процесі проходження служби в Корпусі оперативно-раптової дії. Запропоновано класифікацію видів службової дисципліни та визначено особливості кожного з них. За результатами дослідження запропоновано конкретні кроки удосконалення цих правових категорій в процесі служби, за допомогою внесення змін до профільних законодавчих актів. Відзначено, що дисципліна в органах поліції - це суворе і точне виконання поліцейськими відповідно до порядку і правил, встановлених законодавством України, службових обов'язків, реалізація ними своїх повноважень і дотримання обмежень за посадою в процесі своєї службової діяльності. Метою даної статті є вивчення існуючої нормативно-правової бази, що регулює діяльність органів Національної поліції України та, зокрема, спецпідрозділу КОРД, встановлення основних особливостей дотримання дисципліни і законності службовцями, а також розробка конкретних шляхів удосконалення зазначених правових категорій в процесі служби. Дослідження проводилося з використанням формально-логічного, порівняльно-правового та чисто юридичних методів.
Sirokha D. Basic aspects of the compliance with discipline and legitimacy within the official activities of police / D. Sirokha, V. Felyk, Y. Podorozhnii, A. Podorozhnii // Amazonia Investiga. – V. 9(25). – Universidad de la Amazonia, 2020. – P. 487-492.
Keywords: discipline; self-discipline; departmental officers’ rights; special division; дисциплина; самодисциплина; права сотрудников ведомств; спецподразделение; дисципліна; самодисципліна; права співробітників відомств; спецпідрозділ; Research Subject Categories::LAW/JURISPRUDENCE